2017
DOI: 10.1007/s10877-017-0095-y
|View full text |Cite
|
Sign up to set email alerts
|

The pressure exerted on the tongue during intubation with simultaneous cervical spine immobilisation: a comparison between four videolaryngoscopes and the Macintosh laryngoscope—a manikin study

Abstract: Excessive pressures exerted on the tongue during intubation may be associated with serious complications and may make intubation more difficult. The aim of this study was to evaluate five different intubating devices in the hands of experienced anaesthetists during simulated conditions of reduced cervical spine mobility. Forty senior anaesthetists participated in the study (female = 18, male = 22). The mean pressure exerted on the tongue during intubation was recorded with a standard manometer. The overall int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Most anesthesiologists are more familiar with direct laryngoscopy, but we couldn't analyze the level of experience in our review, as the level of experience with video-laryngoscopes or advanced airway technology has not been consistently reported. While previous studies have demonstrated a lower force applied on the teeth [35], the tongue [36], and the glottis [37] in patients undergoing video-laryngoscopy compared to direct laryngoscopy, this is, to our knowledge, the first study to systematically evaluate the incidence of intubation related injury in Video-assisted compared to direct laryngoscopy. The data obtained from the analysis of studies may suggest the superiority of particular methods of management; however, the clinical decision concerning the use of particular types of laryngoscopes must depend on the practice and protocols of a given institution as well as individual experience in the use of a given device and anatomical conditions of a specific patient.…”
Section: Discussionmentioning
confidence: 81%
“…Most anesthesiologists are more familiar with direct laryngoscopy, but we couldn't analyze the level of experience in our review, as the level of experience with video-laryngoscopes or advanced airway technology has not been consistently reported. While previous studies have demonstrated a lower force applied on the teeth [35], the tongue [36], and the glottis [37] in patients undergoing video-laryngoscopy compared to direct laryngoscopy, this is, to our knowledge, the first study to systematically evaluate the incidence of intubation related injury in Video-assisted compared to direct laryngoscopy. The data obtained from the analysis of studies may suggest the superiority of particular methods of management; however, the clinical decision concerning the use of particular types of laryngoscopes must depend on the practice and protocols of a given institution as well as individual experience in the use of a given device and anatomical conditions of a specific patient.…”
Section: Discussionmentioning
confidence: 81%
“…For example, the degree of force that can be safely applied to the soft tissues such as the tongue and posterior oropharynx and the degree of torque used to manipulate the airway in order to expose the trachea with the laryngoscope are essentially unknown. While a number of investigators have begun to study these factors in simulated and real adult patients [19,20,21,22,23,24,25,26,27,28,29], this data cannot be directly translated to neonatal patients due to different equipment used and the large differences in patient weight and size. Furthermore, the immature and more delicate tissues of newborns are at greater risk of trauma, and their anterior tracheal anatomy can make intubation more challenging than in older patients.…”
Section: Physical Ergonomic Challengesmentioning
confidence: 99%